2020
DOI: 10.1002/fam.2881
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of design fires and particle emissions to be used in performance‐based fire design of nuclear facilities

Abstract: Summary CERN operates one of the most complex particle accelerator facilities in the world. Several different hazards, including fires, are present and need to be investigated and reduced to a tolerable level. Toward this goal, CERN aims at developing a catalog containing detailed fire dynamics descriptions of combustible items present in its facilities. This paper contributes to this catalog in two ways. First, through the development of a design fire calculator for electrical cabinets that allows the determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the early fire, combustibles generally release smoke in the stages of pyrolysis and smoldering 1 . Therefore, smoke detectors exhibit faster responses to fires when compared to other types of fire detectors that detect flames, heat, and gases 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the early fire, combustibles generally release smoke in the stages of pyrolysis and smoldering 1 . Therefore, smoke detectors exhibit faster responses to fires when compared to other types of fire detectors that detect flames, heat, and gases 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that size distribution of particles obtained from thermal cutting of metals was associated with cutting parameters such as cutting materials, cutting methods, cutting conditions [15,16]. Many studies revealed that open burning of insulated copper wire and electronic waste released small particles, PAHs and heavy metals into the atmosphere [17][18][19]. Several findings reported that concentrations of atmospheric particle-bound heavy metals in e-waste recycling areas were significantly higher than those in uncontaminated areas [11,12,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%